Intramedullary Nailing Supplemented with Poller Screws for Proximal Tibial Fractures - Sunil G Kulkarni; Ankit Varshneya; Shreenath Kulkarni; Govind S Kulkarni; Milind G Kulkarni; Vidhisha S Kulkarni; Ruta M Kulkarni (Journal of Orthopaedic Surgery, 2012)
Purpose. To evaluate outcome of intramedullary nailing supplemented with Poller screws for proximal tibial fractures using small diameter nails. Methods. 50 men and 20 women (75 fractures) aged 18 to 65 (mean, 33) years underwent intramedullary nailing supplemented with Poller screws for acutely displaced fractures (n=60) or for delayed union (n=10) or mal-union (n=5) of the proximal metadiaphyseal tibia. 88% of the fractures were caused by road traffic accidents. 54 cases had closed fractures and 21 had grade I or II compound fractures. Clinical and radiological outcome was evaluated. Results. In 69 cases, healing occurred after a mean of 4.2 (range, 3–9) months. In 5 cases, there was nonunion, which was resolved by bone grafting. One case was mal-united. 63 patients recovered a full range of knee motion (0°–130°), and the remaining 7 attained flexion of 0° to 90°. According to the knee rating scale of the Hospital for Special Surgery, outcome was excellent in 50 patients, good in 14, poor in 3, and failed in 3 at month 12, and remained so after a mean follow-up of 30.8 months. Postoperatively, 74 cases had <5° of varus or valgus malalignment, and only one developed varus of +7°. 65 cases exhibited no deformity, 7 had a deformity of <3°, and 3 had a deformity of 4° to 9°. Conclusion. Poller screws help maintain fixation of intramedullary nailing and alignment of fractures.